2021
DOI: 10.1186/s11689-020-09354-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for decreased parasympathetic response to a novel peer interaction in older children with autism spectrum disorder: a case-control study

Abstract: Background Individuals with autism spectrum disorder (ASD) often experience elevated stress during social interactions and may have difficulty forming and maintaining peer relationships. The autonomic nervous system (ANS) directs physiological changes in the body in response to a number of environmental stimuli, including social encounters. Evidence suggests the flexibility of the ANS response is an important driving factor in shaping social behavior. For youth with ASD, increased stress respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…Kushki et al ( 27 ) and Muscatello et al ( 30 ) did not observe baseline RSA differences. Corbett et al reported that children with ASD did not show poor autonomic regulation during social interaction with novel peers, based on similar RSA values ( 31 ).…”
Section: Critical Analysis Of Hrv Parameter Assessmentsmentioning
confidence: 88%
See 3 more Smart Citations
“…Kushki et al ( 27 ) and Muscatello et al ( 30 ) did not observe baseline RSA differences. Corbett et al reported that children with ASD did not show poor autonomic regulation during social interaction with novel peers, based on similar RSA values ( 31 ).…”
Section: Critical Analysis Of Hrv Parameter Assessmentsmentioning
confidence: 88%
“…Muscatello et al ( 30 ) studied the pre-ejection period, and no difference was found related to social tasks. However, the pre-ejection period is a measure of ventricular contractility and is not a good measure of general sympathetic functioning ( 59 ).…”
Section: Assessment Of Sympathetic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…An invention in our experimental design is that we combined interpersonal distance measurement with heart rate registration. In social behaviour parasympathetic regulation, the flexibility of vagal tone plays an important role according to Porges' polyvagal theory (Muscatello et al, 2021;Porges, 2003Porges, , 2009. Resting high-frequency HRV was found to be associated with cooperative behaviour, using less disengagement and more socially adaptive emotion regulation strategies among healthy adults (Beffara et al, 2016;Geisler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%